Ozone Levels Associated to the Photochemical Smog in Santiago of Chile. the Elusive Rol of Hydrocarbons - Lissi-Gervaso, E; Rubio-Campos, M (Sociedad Chilena de Quimica, 2011)
Santiago of Chile presents, in autumn and summer, high levels of oxidants and, in particular of ozone. Peculiar features of this phenomenon are a strong dependence of the contamination with the daily maxima temperature and a weekend effect, comprising relatively high ozone levels in spite of reduced emissions of its precursors. A common explanation of these effects could be an increase in the VOCs/NOx ratio. In order to test this possibility we perform la multiparametric analysis of Santiago s historical data. This data treatment corroborates a robust dependence of maxima ozone levels with temperature and a moderate weekend effect. In fact, ozone levels in weekend days are similar to those of working days, in spite of significantly reduced primary emissions (29 % of NOx and 20 % of CO). However, no increase in VOC s/NOx ratios, measured at the early morning rush out hours, is observed in high temperature days. On the other hand, the data suggest a moderate increase of the VOCs/NOx ratio in week ends. This would indicate that other factors beyond a simple increase in VOC s levels contribute to the above mentioned peculiarities of oxidant levels in the urban atmosphere of Santiago.